Oral anticoagulation and clinical outcomes in COVID-19: An Italian multicenter experience - Schiavone, Marco; Gasperetti, Alessio; Mancone, Massimo; Curnis, Antonio; Mascioli, Giosuè; Mitacchione, Gianfranco; Busana, Mattia; Sabato, Federica; Gobbi, Cecilia; Antinori, Spinello; Galli, Massimo; Forleo, Giovanni Battista (International journal of cardiology, 2021)
Since the body of evidence addressing the coagulation derangements caused by Coronavirus disease (COVID-19) has been constantly growing, we investigated whether pre-hospitalization oral anticoagulation (OAC) or in-hospital heparin treatment could have a protective role among COVID-19 patients. In this cohort study, consecutive COVID-19 patients admitted to four different Italian Institutions were enrolled. Baseline demographic, clinical, laboratory, and radiological characteristics, as well as in-hospital treatment and outcomes were evaluated. The primary outcome was mortality. A total of 844 COVID-19 patients were enrolled as study cohort, n = 65 (7.7%) taking OACs prior to hospitalization. Regarding clinical outcomes, OAC patients developed acute hypoxemic respiratory failure (AHRF) more frequently than non-OAC patients as well as presenting a higher mortality rate (44.6% vs 19.8%, p < 0.001). At overall multivariate logistical regression, use of heparin (n = 394, 46.6%) was associated with a better chance of survival to hospital discharge (OR 0.60 [0.38–0.94], p < 0.001), in particular in patients with AHRF, with no association found with the use of OACs. In a sub-analysis, the highest mortality rate was found for AHRF patients when heparin was not administered. In our cohort, OACs appeared to be ineffective in reducing mortality rate, while heparin resulted to be a useful treatment when lung disease was sufficiently severe, potentially suggesting a crucial role of microthrombosis in severe COVID-19. Due to the relatively small number of COVID-19 patients treated with OACs included in our analysis and their higher number of comorbidities, larger studies are needed in order to confirm our findings. •Evidence on a prothrombotic asset caused by COVID-19 has been constantly growing.•In our cohort, OACs appeared to be ineffective in reducing mortality rate.•Heparin resulted to be a useful treatment when lung disease was sufficiently severe.•Microthrombosis may have a crucial role in COVID-19.•Due to the relatively small sample size of OAC patients included, larger studies are needed.